Preferences for Donating to Religious and Non-Religious Philanthropic Institutions: Evidence in Indonesia - Hidayah, Nur; Ade, Nur Syam (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This research aims to determine the factors influencing online donation decisions in religious and non-religious philanthropic institutions. 105 questionnaires were disseminated to the respondents in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi), Indonesia, and analyzed using logistic regression. The findings reveal that in religious philanthropic institutions, the impact has a significant effect, while ease of use, convenience, and innovation have no effect on online donation decisions. In non-religious philanthropic institutions, convenience, innovation, and impact have a significant effect, while ease of use has no effect on online donation decisions. There is a slight difference in factors influencing online donation decisions in religious and non-religious philanthropic institutions. Religious philanthropic institutions should expand their impact to raise their donors. Meanwhile, non-religious philanthropic institutions should improve the quality of their digital platform and expand the innovation and impact of the programs to increase their donors.JEL Classification: D64, L31, Z12How to Cite:Hidayah, N., & Ade, N. S. (2023). Preferences for Donating to Religious and Non-Religious Philanthropic Institution: Evidence in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 191-206. https://doi.org/10.15408/sjie.12ii1.27887.